2001
DOI: 10.1073/pnas.191389598
|View full text |Cite
|
Sign up to set email alerts
|

A physiological role for oxalic acid biosynthesis in the wood-rotting basidiomycete Fomitopsis palustris

Abstract: A metabolic mechanism for oxalic acid biosynthesis in the woodrotting basidiomycete Fomitopsis palustris has been proposed on the basis of biochemical analyses of glucose metabolism. There was a strong correlation between glucose consumption and oxalate production. Oxalic acid was found to accumulate in the culture fluid in about 80% of the theoretical yield or about 5-fold, on the basis of the fungal biomass harvested. The results clearly indicate that glucose was not completely oxidized to CO2 by the tricarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
113
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(122 citation statements)
references
References 43 publications
6
113
2
1
Order By: Relevance
“…4A and C), but decreased after day 5 of cultivation through the stationary phase (Day 5, 126.1 · 10 7 ; Day 13, 30.9 · 10 7 copy number/0.2 lg total RNA). The profile was consistent with changes in FPICL1 activity during cultivation [6]. Accordingly, the results suggest that expression of the gene encoding FpTRP26 was positively correlated with OA-accumulation, whereas FPICL1 gene expression was related with the growth phase.…”
Section: Possible Involvement Of Fptrp26 In Oxalic Acid Resistancesupporting
confidence: 77%
See 2 more Smart Citations
“…4A and C), but decreased after day 5 of cultivation through the stationary phase (Day 5, 126.1 · 10 7 ; Day 13, 30.9 · 10 7 copy number/0.2 lg total RNA). The profile was consistent with changes in FPICL1 activity during cultivation [6]. Accordingly, the results suggest that expression of the gene encoding FpTRP26 was positively correlated with OA-accumulation, whereas FPICL1 gene expression was related with the growth phase.…”
Section: Possible Involvement Of Fptrp26 In Oxalic Acid Resistancesupporting
confidence: 77%
“…FPICL1 was chosen, because FPICL1 is important during the early grow period of F. palustris on glucose [6,8,12]. The amount of FpTRP26 transcripts increased concomitantly with the accumulation of OA (Fig.…”
Section: Possible Involvement Of Fptrp26 In Oxalic Acid Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…6). A metabolic shunt between the citric acid and glyoxylate cycles is central to oxalic-acid accumulation by the brown-rot fungus Fomitopsis palustris (21). Analysis of the P. placenta genome demonstrates a functional glyoxylate shunt and substantially extends our understanding of the number, structure, and transcription of key genes ( Fig.…”
Section: Modification Of Lignin and Other Aromatic Compoundsmentioning
confidence: 97%
“…Paxillus involutus has also been shown to produce oxalic acid by using bicarbonate ions (Lapeyrie 1988) whereas Hysterangium crassum on Douglas-fir was found to extract Fe and Al from andesite by providing high amounts of oxalate for chelation (Cromack Jr. et al 1979). Munir et al (2001) indicated that wood-rotting basidiomycetes oxidize glucose to oxalate in order to generate energy. Wallander and Wickman (1999) showed that Pinus sylvestris (L.) seedlings colonized by Suillus variegatus appeared to be more efficient in the uptake of K from biotite than from microcline.…”
mentioning
confidence: 99%